Expanding the diversity of Chardonnay aroma through the metabolic interactions of Saccharomyces cerevisiae cocultures - Bordet, Fanny; Romanet, Rémy; Bahut, Florian; Ballester, Jordi; Eicher, Camille; Peña, Cristina; Ferreira, Vicente; Gougeon, Régis; Julien-Ortiz, Anne; Roullier-Gall, Chloé; Alexandre, Hervé (Frontiers in Microbiology, 2023)
Yeast co-inoculations in winemaking are often studied in the framework of modulating the aromatic profiles of wines. Our study aimed to investigate the impact of three cocultures and corresponding pure cultures of S. cerevisiae on the chemical composition and the sensory profile of Chardonnay wine. Co-culture makes it possible to obtain completely new aromatic expressions that do not exist in the original pure cultures attributed to yeast interactions. Esters, fatty acids and phenol families were identified as affected. The sensory profiles and metabolome of the cocultures, corresponding pure cultures and associated wine blends from both pure cultures were found to be different. The coculture did not turn out to be the addition of the two pure culture wines, indicating the impact of interaction. High resolution mass spectrometry revealed thousands of cocultures biomarkers. The metabolic pathways involved in these wine composition changes were highlighted, most of them belonging to nitrogen metabolism.